Acute viral hepatitis - Dusheiko, Geoffrey (Henry Stewart Talks, 2012)
Acute viral hepatitis: causes, signs, symptoms and diagnosis, Acute liver failure including epidemiology, Acute hepatitis A (diagnosis, clinical & serological course, complications, management, prevention & control), Acute hepatitis B (virology, geo-distribution, immune response, pregnancy, clinical & serological course, epidemiology, treatment, prevention), Chronic Hepatitis B, Hepatocellular carcinoma, Acute hepatitis C (prevalence, diagnosis, clinical course, transmission, immune clearance, management), Hepatitis C chronic hepatitis, Acute hepatitis D (virology, epidemiology, diagnosis, transmission), Chronic hepatitis D, Coinfection versus superinfection (HBV, HDV), Acute hepatitis E (distribution, epidemiology, diagnosis, clinical & serological course, management), Chronic hepatitis E, Currently available oral antivirals
Archived at 2019/06/13